CORRELATION OF MEDICAL PROFESSIONALISM WITH ACADEMIC PERFORMANCE IN FINAL YEAR MEDICAL STUDENTS - Murtaza, Badar; Ashar, Abid; Sabir, Sohail (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the correlation of medical professionalism score of final year medical students with their academic results of the final professional examination. Study Design: Correlational study. Place and Duration of Study: Army Medical College, Rawalpindi, from Mar to Nov 2019. Methodology: Final year medical students were enrolled by non-probability consecutive sampling. Their medical professionalism score was calculated using the Penn State College of Medicine-Professionalism Questionnaire (PSCOM-PQ). All the aspects of accountability, altruism, excellence, duty, honour/integrity and respect were noted using the questionnaire. Thirty points from the questionnaire were used, calculating the maximum value of 150. After the final professional examination, their academic results were procured. The strength of the relationship between medical professionalism score and academic results of final year professional examination was assessed using the Pearson correlation coefficient. Results: A total of 75 final year medical students were studied. The age ranged from 22-27 years (23.96 ± 1.16 years). The male to female ratio was 2.12:1. The medical professionalism score ranged from 71-150 points (127.28 ± 15.43). The academic results percentages of final year professional examination (MBBS) were not found to be significantly correlated with their professionalism score (r=-0.10, p=0.394). Conclusion: The medical professionalism score of the final year medical students has no statistically significant correlation with their academic performance.